(D+1)-Colored Graphs - a Review of Sundry Properties - Ryan, J.P. (Symmetry, Integrability and Geometry: Methods and Applications, 2016)
We review the combinatorial, topological, algebraic and metric properties supported by (D+1)-colored graphs, with a focus on those that are pertinent to the study of tensor model theories. We show how to extract a limiting continuum metric space from this set of graphs and detail properties of this limit through the calculation of exponents at criticality.